Achievement Goals and their Underlying Goal Motivation: Does it Matter Why Sport Participants Pursue their Goals? - Patrick Gaudreau (Psychologica Belgica, 2016)
This study examined whether the good or bad outcomes associated with mastery-approach (MAP) and performance-approach (PAP) goals depend on the extent to which they are motivated by autonomous or controlled motivation. A sample of 515 undergraduate students who participated in sport completed measures of achievement goals, motivation of achievement goals, perceived goal attainment, sport satisfaction, and both positive and negative affect. Results of moderated regression analyses revealed that the positive relations of both MAP and PAP goals with perceived goal attainment were stronger for athletes pursuing these goals with high level of autonomous goal motivation. Also, the positive relations between PAP goals and both sport satisfaction and positive affect were stronger at high levels of autonomous goal motivation and controlled goal motivation. The shape of all these significant interactions was consistent with tenets of Self-Determination Theory as controlled goal motivation was negatively associated with positive affect and sport satisfaction and positively associated with negative affect. Overall, these findings demonstrated the importance of considering goal motivation in order to better understand the conditions under which achievement goals are associated with better experiential and performance outcomes in the lives of sport participants.